The screen printing of a power-law fluid (vol 73, pg 93, 2012) - Taroni, M; Breward, C; Howell, P; Oliver, J; Young, R (2012)
We present a two-dimensional large-aspect-ratio model for the off-contact screen printing of a power-law fluid. We extend the work of White et al. (J Eng Math 54:49-70, 2005) by explicitly including the fluid/air free surface that is present beneath the screen ahead of the squeegee. In the distinguished parameter limit of greatest interest to industry, the process is quasi-steady on the time-scale of a print and can be analysed in three separate regions using the method of matched asymptotic expansions. This allows us to predict where the fluid transfers through the screen, the point at which it first makes contact with the substrate, and the amount of fluid deposited on the substrate during a print stroke. Finally, we show that using a shear-thinning fluid will decrease the amount of fluid transferred ahead of the squeegee, but increase the amount of fluid deposited on the substrate. © 2011 Springer Science+Business Media B.V.